CONTINUITY OF MIDWIFERY CARE FOR MRS. B WITH SECOND-DEGREE PERINEAL RUPTURE AT PMB PERA, MEDAN TUNTUNGAN DISTRICT, NORTH SUMATRA PROVINCE, IN 2025 - Siska Wulandari Telaumbanua; Manullang, Rasmi; Singarimbun, Perawati; Shinta Olivia Hia; Tumangger, Wilma Riana; Mardiana; Gebryella (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Perineal rupture is a tear in the perineum occurring during delivery, either spontaneously or through instrumental assistance. These tears often occur along the midline and can become extensive if the fetal head is delivered too rapidly. Key contributing factors include parity, birth weight, and the duration of the second stage of labor. Objective:This study aims to provide and analyze comprehensive midwifery care for Mrs. B, specifically focusing on the management and prevention of perineal rupture. Methods: A descriptive case study approach was employed using Continuity of Care (CoC). The care was implemented through the Helen Varney midwifery management method and documented using SOAP notes, spanning from pregnancy and childbirth to newborn care, postpartum, and family planning. Results: The study identified that proper management of the second stage of labor and controlled delivery techniques are crucial in minimizing spontaneous perineal tears. Mrs. B received integrated education on perineal health and postpartum recovery. Conclusion: Continuous midwifery care using the Varney method effectively monitors risk factors and ensures the delivery of high-quality, comprehensive care to reduce maternal morbidity related to perineal trauma.